The tricyclic antidepressants amitriptyline, nortriptyline and imipramine are weak antagonists of human and rat alpha(1B)-adrenoceptors - Nojimoto, F. D. [UNESP]; Mueller, A. [UNESP]; Hebeler-Barbosa, F. [UNESP]; Akinaga, J. [UNESP]; Lima, V. [UNESP]; de A Kiguti, L. R. [UNESP]; Pupo, A. S. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2010)
Although it is long known that the tricyclic antidepressants amitriptyline, nortriptyline and imipramine inhibit the noradrenaline transporter and alpha(1)-adrenoceptors with similar affinities, which may lead to self-cancelling actions, the selectivity of these drugs for alpha(1)-adrenoceptor subtypes is unknown. The present study investigates the selectivity of amitriptyline, nortriptyline and imipramine for human recombinant and rat native alpha(1)-adrenoceptor subtypes. The selectivity of amitriptyline, nortriptyline and imipramine was investigated in HEK-293 cells expressing each of the human alpha(1)-subtypes and in rat native receptors from the vas deferens (alpha(1A)), spleen (alpha(1B)) and aorta (alpha(1D)) through [H-3]prazosin binding, and noradrenaline-induced intracellular Ca2+ increases and contraction assays. Amitriptyline, nortriptyline and imipramine showed considerably higher affinities for alpha(1A)- (similar to 25- to 80-fold) and alpha(1D)-adrenoceptors (similar to 10- to 25-fold) than for alpha(1B)-adrenoceptors in both contraction and [H-3]prazosin binding assays with rat native and human receptors, respectively. In addition, amitriptyline, nortriptyline and imipramine were substantially more potent in the inhibition of noradrenaline-induced intracellular Ca2+ increases in HEK-293 cells expressing alpha(1A)- or a truncated version of alpha(1D)-adrenoceptors which traffics more efficiently towards the cell membrane than in cells expressing alpha(1B)-adrenoceptors.Amitriptyline, nortriptyline and imipramine are much weaker antagonists of rat and human alpha(1B)-adrenoceptors than of alpha(1A)- and alpha(1D)-adrenoceptors. The differential affinities for these receptors indicate that the alpha(1)-adrenoceptor subtype which activation is most increased by the augmented noradrenaline availability resultant from the blockade of neuronal reuptake is the alpha(1B)-adrenoceptor. This may be important for the behavioural effects of these drugs. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Tricyclic antidepressants; alpha(1)-Adrenoceptor subtypes; Amitriptyline; Nortriptyline; Imipramine